Determinants of Traffic Accidents in Motorcycle Riders: Literature Review - Tira Octavia, Adinda; Wahyuningtias, Cica; Luthviatin, Novia (Health Science UDINUS, 2025)
Traffic accidents are one of the biggest causes of death in Indonesia. Data for 2022 shows that there were 85,691 traffic accidents involving motorbike riders. The high death rate due to accidents will have an impact on people's welfare. There are several factors that cause traffic accidents, namely demographic characteristics, unsafe conditions, and unsafe actions. The aim of this research is to determine the determinants of traffic accidents among motorcyclists. This research uses library research or literature study, which involves 30 articles that are the subject of the study. Article search via Elsevier, DOAJ, ScienceDirect, ResearchGate, Google Scholar, and Garuda databases. The inclusion criteria were articles from 2018-2023 that analyzed the determining factors of traffic accidents for motorcyclists. Determining factors for traffic accidents for motorcyclists include demographic characteristics, namely age, gender, and knowledge; unsafe conditions in the form of vehicle factors, road conditions, and weather conditions; and unsafe actions in the form of not wearing a helmet, behavior under the influence of alcohol, aggressive driving, and drowsiness. Things that can be suggested are related to age restrictions for driving, increasing knowledge of traffic rules, improving road conditions, vehicle guidance standards, knowledge of the weather, and increasing compliance in driving.